Effects of milk thistle seed against aflatoxin B(1) in broiler model - Amiridumari, Halimeh (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Consumption of aflatoxin B(1) (AFB(1)) contaminated products can pose a risk of development of various diseases in human and animals due to radical production. The scope of this work is to evaluate the efficacy of milk thistle seed (MTS), as a radical scavenger, on serum biochemistry, lipid profile and liver enzymes against AFB(1) in broiler chickens contaminated with AFB(1). MATERIALS AND METHODS: The effect of nine experimental treatments (3 × 3 factorial design) was assessed using 216 one-d-old Ross 308 male broiler chicks in a randomized complete design with four replicates of six birds for each dietary treatments: Control (T1), 250 ppb AFB(1) (T2), 500 ppb AFB(1) (T3), 0.5% MTS (T4), 0.5% MTS Plus 250 ppb AFB(1) (T5), 0.5% MTS Plus 500 ppb AFB1 (T6), 1.0% MTS (T7), 1.0% MTS Plus 250 ppb AFB(1) (T8), and 1.0% MTS Plus 500 ppb AFB(1) (T9). The individual and combined effects of dietary AFB(1) and MTS on serum biochemistry factors (Glucose, Calcium, Phosphorus, Iron, Creatinine, and Uric acid), lipid profile (Triglyceride, Cholesterol, Low density lipoprotein (LDL), and High density lipoprotein (HDL)) and liver enzymes aspartate amino-transferase and alanine amino-transaminase (ALT) in broilers were evaluated at 21 days of age. Also, statistical packages Macros-1.002 (2010) were used to perform the above analysis on computer. RESULTS: Consumption of 500 ppb AFB(1) in to the diet significantly decreased HDL (58.13 ± 2.65), Calcium (7.11 ± 0.13), and Glucose (197.1 ± 7.42) compared to the control group (85.12 ± 1.95, 9.45 ± 0.17 and 223.1 ± 6.61, respectively), (P < 0.05). In contrast, it significantly increased creatinine (2.25 ± 0.011) and AST (244.51 ± 4.91). Using MTS together with AFB(1) significantly reduced the effect of AFB(1) on the above parameters. CONCLUSION: MTS can provide protection against the negative effects of AFB(1) on broiler chicks.